Overview of the Implementation of the No Smoking Area (KTR) Policy in the Indonesian Campus Environment: Literature Review - Hamidah Qudus; Ella Nurlaella Hadi (Journal of Social Research, 2023)
Every teaching and learning place (including campuses) is required to implement the No Smoking Area Policy (KTR) in accordance with Law on Health No. 36 of 2009. The campus itself is one of the seven KTR areas in Indonesia. The smoking ban policy in seven KTR areas is expected to reduce the prevalence of Indonesian smokers and control risk factors for non-communicable diseases caused by smoking The purpose of this study is to know and obtain an overview of the implementation of KTR policies in the Indonesian campus environment. This research uses systemic literature review design by studying articles. The reviewed articles use qualitative studies. There were 2120 articles according to keywords and were selected again into 9 articles according to the topic, namely about KTR policies in the Indonesian campus environment. The articles used were published between 2015 and 2020. That the KTR implementation policy has been implemented on Indonesian campuses but has not been optimal with various problems. The problems encountered were lack of socialization, no KTR supervision system, no enforcement of rules, no data collection and evaluation as well as factors of smoking habits. The implementation of campus KTR policy is considered not going well and optimally because there are many violations and implementation obstacles in the form of socialization, law enforcement, monitoring, and evaluation of KTR.